Angiograhic profile and in-hospital outcome of young patients presenting with ST Elevation Myocardial Infarction (STEMI) in tertiary cardiac hospital - Pandey, Rabindra; Maskey, Arun; Shrestha, Bishal; Budhathoki, Arjun; Malla, Sabindra Bhupal; Baniya, Bibek; Bhatta, Surendra; Shrestha, Sashit; Yadav, Parveen Kumar (Journal of Advances in Internal Medicine, 2021)
Objective: To assess the angiographic profile and in hospital outcomes of primary percutaneous coronary intervention among young patients presenting with acute ST Elevation Myocardial Infarction and underwent primary PCI. Methods: The retrospective observational study was conducted at Shahid Gangalal National Heart Centre (SGNHC), Kathmandu, from july 2020 to June 2021, and included acute ST-Elevation Myocardial Infarction patients underwent primary percutaneous coronary intervention (PCI). Data was collected on demographic, angiographic, and in-hospital outcomes. Patients <45 years were considered young. Data was analysed using SPSS 21. Results: Total 104 patients met the inclusion criteria. Mean age of presentation was 40.16 ± 4.42 years. Over three-fourth of the patients were male 80 (76.9%). Smoking was the most prevalent risk factor with 61 (58.6%) patients followed by hypertension 35 (33.6%) and dyslipidemia 23 (22.1%). Single Vessel Disease (SVD) was the most common finding seen in 62 patients (59.6%) and Left Anterior Descending Artery (LAD) was the most commonly involved artery seen in approximately three fourth patients 80 (76.9%) followed by RCA 61 (58.6%) and LCX 15(14.4%). Left Main Coronary Artery is involved in 3 patients (2.9%). 6 (5.8%) patients suffered from cardiogenic shock either at admission or during hospital stay. Total In hospital mortality was seen in 3 (2.9%) patients. Conclusions: Among young patients (<45 years old) with STEMI who underwent PPCI in underdeveloped country majority are males and smoking is the most prevalent risk factor. Single vessel disease and LAD involvement is the most common angiographic finding and they have favorable in-hospital outcome.